Common Cases in Women's Primary Care Clinics - Mahmoudi, Massoud; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2024)
This book offers a comprehensive overview of common medical conditions that present in women's primary care clinics. Medical conditions often present differently in women than they do in men and as a result, primary care providers should be familiar with how to identify and treat these conditions. This book provides a collection of common medical conditions and aims to educate the reader on how to approach and manage such conditions. Chapters cover non-infection conditions, infectious conditions, and health maintenance in women. Common Cases in Women's Primary Care Clinics will be a valuable resource for primary care providers, internists, family practitioners, nurse practitioners, physical assistants, medical students, and other physicians interested in women's primary care conditions. .
Part 1: Introduction -- Chapter 1. Introduction to Women's Primary Care -- Chapter 2. History and Physical Examination of Women -- Chapter 3. Procedures in Women's Primary Care Clinic -- Part 2: Non-Infection Medical Conditions in Women -- Chapter 4. Pelvic Pain -- Chapter 5. Vaginitis -- Chapter 6. Menstrual Disorder -- Chapter 7. Breast Complaints -- Chapter 8. Urinary Incontinence -- Chapter 9. Sexual Dysfunction -- Chapter 10. Intimate Partner Violence (IPV) -- Chapter 11. Women and Immune System -- Chapter 12. Cardiovascular Disease in Women -- Chapter 13. Birth Control -- Chapter 14. Non OB Treatment of the Pregnant Patient -- Chapter 15. Menopause -- Chapter 16. Osteoporosis -- Part 3: Common Infections in Women -- Chapter 17. Urinary Tract Infection -- Chapter 18. Sexually Transmitted Diseases -- Part 4: Health Maintenance -- Chapter 19. Mammography / Cervical Cancer Screening -- Chapter 20. Transgender Care. .
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Primary care (Medicine).; Gynecology .; Primary Care Medicine; Gynecology